Supply Chain Analysis and Development Strategy of Goat Milk Processing at Maleosan Farm, North Sulawesi - Wantasen, Erwin; Umboh, Sintya, J.K; Leke, Jein Rinny (Jurnal Ilmu-Ilmu Peternakan, 2025)
Maleosan Farm is the only goat milk processing facility in North Sulawesi, producing pasteurized milk from Etawa Crossbreed goats. This study analyzed the supply chain flow, value-added generation, and formulated development strategies for pasteurized goat milk production. Using purposive sampling, we collected data from 55 partner farmers, 18 milk collectors, and key stakeholders through structured interviews and observations between January and February 2025. Supply chain mapping, Hayami value-added analysis, and Key Success Factor Analysis were employed. The results showed that the supply chain involved six main actors with bidirectional information flow. Value-added ratios ranged from 36.34% (chocolate), 36.84% (strawberry), to 37.63% (original flavor), generating profits of IDR 17,810-18,656 per liter. Government support emerged as the primary driving factor (TWV=2.89), while limited capital was the main constraint (TWV=2.80). Establishing a cooperative-based partnership system is recommended to address capital limitations and optimize government support for sustainable development.